SUBSURFACE CHARACTERIZATION TO DETERMINE A SUITABLE BOREHOLE LOCATION FOR IRRIGATION AT COLLEGE OF AGRICULTURE, MOKWA NUPE BASIN, NIGERIA - Usman, Yusuf Tanko (FUDMA JOURNAL OF SCIENCES, 2020)
A geo-electric survey involving 15 points Vertical Electrical Sounding and Induced Polarization was carried out to determine positions for the drilling of boreholes that will provide adequate water supply for extensive irrigation work at Niger State College of Agriculture Mokwa, Nigeria. The data were acquired with Schlumberger configuration at stations chosen across the study area. The acquired data were interpreted with IPI2WIN iterative computer software. The interpreted results suggest three geo-electric layers. Their equivalent geologic/lithological units suggest weathered and fractured basement as the aquiferous layers along the three profiles investigated within the study area. Suitable sites for construction of boreholes were outlined based on the aquifer thickness range of the aquiferous layers. The VES 4 & 5 along the first Profile was the most probable and viable site with the highest aquiferous thickness of 19.21 m, followed by the third profile with aquifer thickness of 11.88
Keywords: Aquifer, Borehole, Irrigation, Vertical Electrical Sounding (VES), Induced Polarization